Modeling and simulation of vibratory coupling characteristics of a wind turbine - Keenan Kon (2023)
Wind turbines are a growing phenomenon in the renewable energy sector. To study wind turbines, one important detail not to be overloocked is to predict the responses of the system for various cases of operating conditions.